2022
DOI: 10.1177/23259671221093685
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Harvest of an Osseous-Based Quadriceps Tendon Autograft Results in Thinner Remaining Patellar Bone

Abstract: Background: Patellar fracture after quadriceps tendon (QT) autograft harvest for anterior cruciate ligament reconstruction (ACLR) has been reported in up to 8.8% of patients. Purpose: To determine the thickness of the remaining patellar bone across the QT graft harvest location while providing clinical guidance for safely harvesting a patellar bone block when using a QT graft in ACLR. Study Design: Descriptive laboratory study. Methods: Medial and lateral QT graft boundaries were marked using a bone saw on 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The potential effects of the location and depth of the harvest site have been explored. 22 , 23 Harvesting the bone plug from the lateral portion of the patella 22 and a depth of harvest greater than 50% were associated with fracture. 23 Moreover, Ferrer et al.…”
Section: Discussionmentioning
confidence: 99%
“…The potential effects of the location and depth of the harvest site have been explored. 22 , 23 Harvesting the bone plug from the lateral portion of the patella 22 and a depth of harvest greater than 50% were associated with fracture. 23 Moreover, Ferrer et al.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 41 , 43 A study by Fu et al 10 describes eccentric harvest, harvesting of more than 50% of the anteroposterior thickness or of the mediolateral width, and stress risers at the corner of the graft harvest site as potential risk factors for iatrogenic patellar fracture after QTPB ACLR. 33 In a biomechanical analysis, Perry et al 33 demonstrated significantly less remaining patellar bone in a lateral column QT graft harvest compared with a medial column harvest, potentially demonstrating a risk for patellar fracture.…”
Section: Discussionmentioning
confidence: 99%
“…9 Conversely, harvesting of a patellar bone plug can increase donor-site morbidity and poses a risk for patellar fracture, which has been reported to occur in up to 8.8% of cases, especially when an eccentric harvest is performed. 9,33,36,44 Despite these findings, there have been no significant differences reported regarding complications between the all-soft tissue QT and QTPB techniques.…”
mentioning
confidence: 94%